Education in infection control: A need for European certification. (December 2015) - Zingg, W.; Mutters, N.T.; Harbarth, S.; Friedrich, A.W.
Abstract: Healthcare-associated infections are common adverse events in acute-care medicine, causing significant morbidity and mortality. There has been a significant increase in the commitment to infection prevention and control (IPC) among European countries in recent years. However, there is still heterogeneity in training opportunities and IPC qualifications. The European Union promotes the harmonization of IPC strategies among member states. The European Centre for Disease Prevention and Control (ECDC)-commissioned Training in Infection Control in Europe project sets the stage for harmonization of IPC activities in Europe by issuing a list of core competencies for IPC professionals. European certification of IPC training and professionals would be the next logical step, which must be achieved by close collaboration between different stakeholders in Europe such as the ECDC, the European Society of Clinical Microbiology and Infectious Diseases (ESCMID), the European Union of Medical Specialities, and the national IPC societies. Therefore, the ESCMID has launched the new European Committee on Infection Control to take the lead in the implementation of a European (board) certificate for IPC professionals.